2016
DOI: 10.14419/ijpt.v4i2.5970
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine effects on generation of reactive oxygen species and DNA damage: formation of 8-hydroxydeoxyguanosine in active abusers

Abstract: Cocaine abuse continues to be a major public health problem in the world. An upper numbers of individuals are initiating cocaine use with a stable rate of growth each year with an increasing number of people with cocaine related problems. Following cocaine oxidative pathways a ROS formation are generated. Oxidative stress has been demonstrated to play an important role in cocaine addiction and toxicity due to its oxidized metabolites produced by cytochrome P450 during cocaine biotransformation. The ROS induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Indeed, ROS and OS are believed to play a critical role in smoking dependence and addiction (Kovacic & Cooksy, 2005a; Vargas et al, 2013). In addition, they are implicated in morphine addiction (Ma et al, 2015), methamphetamine addiction (Jang et al, 2017), alcohol addiction, (Kovacic & Cooksy, 2005b), cocaine addiction (Bacchi, Palumbo, Di Carlo, & Coppolino, 2016; Beiser & Yaka, 2019; Jang et al, 2015; Kovacic, 2005), and other abused drugs (Kovacic & Cooksy, 2005c). Indeed, drugs of abuse can provoke epigenetic changes which contribute to addiction via DNA methylation, a process regulated by cellular redox status (Trivedi & Deth, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, ROS and OS are believed to play a critical role in smoking dependence and addiction (Kovacic & Cooksy, 2005a; Vargas et al, 2013). In addition, they are implicated in morphine addiction (Ma et al, 2015), methamphetamine addiction (Jang et al, 2017), alcohol addiction, (Kovacic & Cooksy, 2005b), cocaine addiction (Bacchi, Palumbo, Di Carlo, & Coppolino, 2016; Beiser & Yaka, 2019; Jang et al, 2015; Kovacic, 2005), and other abused drugs (Kovacic & Cooksy, 2005c). Indeed, drugs of abuse can provoke epigenetic changes which contribute to addiction via DNA methylation, a process regulated by cellular redox status (Trivedi & Deth, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The formation of 8 OHdG occurs due to the oxidation of the nitrogenous guanine base, with the addition of HO• in the 8-position carbon, giving rise to a DNA adduct, C8-hydroxy-guanine (8 OHGua). After this process, this molecule ends up losing electrons, giving rise to 8 OHdG (20). Our results demonstrated that immunoexpression for 8 OHdG increased in the group exposed to crack cocaine at 18 mg/kg only.…”
Section: Discussionmentioning
confidence: 58%